Facial Shape, Size, and Gender. Issue 5 (November 2020) - Lambros, Val; Amos, Gideon
Abstract : Summary: Traditional ways of visualizing the differences between male and female faces are often based on single-subject exemplars or artist depictions of hypermasculine and hyperfeminine faces. By equalizing the sizes of male and female facial averages, the authors analyzed the influences of intrinsic shape and size on the architecture of the face. Abstract : Supplemental Digital Content is available in the text.